TERJEMAHAN CERITA PENDEK TOMO-CHAN NO SHIAWASE KARYA YOSHIMOTO BANANA - , SITI ROBIATUL ADAWIYAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This graduating paper project is a translation of short story titled Tomo-chan No Shiawase by Yoshimoto Banana. This short story that tells about a woman who has a family that is not harmonious, and also her love relationships are not so good enough. Selection of this story because it interesting, because in it there are lot of moral messages. In the translation process, the writer applied communicative method. Applying this method, the writer tried to keep the right contextual meaning of the source language, so that both the content and the languange can be accept and understand by the reader. The writer found some difficulties on this graduating paper writing, such as looking for suitable vocabulary in Indonesian language so the reader can understand easily, moreover writer also found new knowledge such as vocabulary, kanji and grammar which writer dont know before.